Agotamiento del derecho de marca, importaciones paralelas y comercio internacional - Benites Arrieta, Gabriel (2023)
The principle of exhaustion of rights is one of the most discussed matters in intellectual property law, forming part of a debate that has not culminated in a global agreement. However, its application is present in all countries and the evaluation of its scope has deserved the attention of the doctrine and the courts of justice of the world. This work focuses on the field of trademarks and tries to show a gene ral perspective on the exhaustion of the right in its presence in international trade, through parallel imports. Likewise, it includes some of the economic reasons that support the existence or restriction of parallel imports, as well as an analysis of their regulation in international trade law.